Profit shifting of multinational corporations worldwide - Javier Garcia-Bernardo; Petr Janský (Charles University in Prague, Institute of Economic Studies (IES), 2023)
We exploit the new country-by-country reporting data of multinational corporations, with unparalleled country coverage, to reveal the distributional consequences of profit shifting. We estimate that multinational corporations worldwide shifted over 850 billion in profits in 2017, primarily to countries with effective tax rates below 10%. Countries with lower incomes lose a larger share of their total tax revenue due to profit shifting. We further show that a logarithmic function is better suited for capturing the non-linear relationship between profits and tax rates than linear or quadratic functions. Our findings highlight effective tax rates' importance for profit shifting and tax reforms.
Keywords: F23; H25; H26; H32; 330; multinational corporation; corporate taxation; profit shifting; effective tax rate; country-by-country reporting; global development